Investigation of shear thickening fluid (STF) impregnated interlayer hybrid composites under low-velocity impact loading - Saricam, Canan; Okur, Nazan (SAGE Publications, 2024)
This study deals with the development of interlayer hybrid composites with improved low-velocity impact response. In the composites produced using the hand lay-up technique, glass, carbon, and Kevlar woven fabrics were used as reinforcement materials and epoxy resin was used as the matrix material. Shear thickening fluid (STF) was impregnated into the fabric for enhancing their performance. The effect of hybridization with different stacking sequences and the impregnation of STF on the peak load, deflection at peak load, energy absorption, impact strength, and damage degree were investigated. All samples were subjected to 3.12 m/s and 4.42 m/s impact velocities using a drop-weight impact tester applying 200J and 400J impact energy levels, respectively. The results revealed that in samples containing neat fabrics, the performances of the pure Kevlar samples were much better in comparison to hybrid samples, especially under high impact energy. However, STF significantly improved the impact strength and energy absorption (up to 30 times) of all samples, including hybrid ones. On the other hand, as the impact energy increased, the use of a Kevlar reinforced plate on the impact surface was crucial, providing higher energy absorption, and no perforation was observed since most of the energy was required to initiate the damage. In the samples with Kevlar in the intermediate layer, however, the majority of the impact energy caused propagation and expansion of the damage. According to the findings, up to 50% cost savings were achieved in STF-impregnated hybrid samples containing Kevlar.